IMPLEMENTATION OF SMALL, MICRO, AND MEDIUM ENTERPRISE (MSME) DEVELOPMENT PROGRAM IN CORPORATE SOCIAL RESPONSIBILITY (CSR) AT PT. PERKEBUNAN NUSANTARA IV REGIONAL 1 MEDAN - Fathin Fauziah; Muhammad Imanuddin Kandias Saraan (OPINI: Journal of Communication and Social Science, 2025)
This study examines the implementation of the Small, Micro, and Medium Enterprise (SME) Development Program within the Corporate Social Responsibility (CSR) framework of PT Perkebunan Nusantara IV (PTPN IV) Regional 1 Medan. Using a descriptive qualitative approach and Matland’s implementation model, the program was evaluated through four indicators: policy accuracy, implementation accuracy, target accuracy, and environmental accuracy. Data were collected through interviews, observations, and documentation from purposively selected informants, including CSR staff and SME actors. The findings show that policy accuracy is strong, as the program aligns with SME needs and the company’s mandate. Implementation accuracy improved significantly after loan management was transferred to Bank BRI, although training activities remain limited by short duration and insufficient mentoring. Target accuracy indicates that the program successfully reaches SMEs near operational areas, despite challenges related to SMEs’ internal readiness. From an environmental perspective, PTPN IV has effectively utilized its authority and networks, though improvements are needed through business-type-based training. Overall, the CSR SME program reflects commitment and adaptability, but its effectiveness can be enhanced through better training design and strengthened mentoring support.